Pharmacist Interventions to Improve Specialty Medication Adherence: Study Protocol for a Randomized Controlled Trial - Amanda M. Kibbons; Megan Peter; Josh DeClercq; Leena Choi; Jacob Bell; Jacob Jolly; Elizabeth Cherry; Bassel Alhashemi; Nisha B. Shah; Autumn D. Zuckerman (Adis, Springer Healthcare, 2020)
Abstract Background The effectiveness of specialty medications in complicated clinical conditions depends on adherence to therapy. However, specialty medications pose unique barriers to adherence. Objective This study aims to determine whether pharmacist interventions improve specialty medication adherence. Methods This is a single-center, pragmatic, randomized controlled trial ongoing since 10 May 2019 at an integrated health system specialty pharmacy. This study evaluates usual care compared with usual care plus patient-tailored adherence interventions. Study design and procedures were informed by focus groups with patients and specialty pharmacists. Patients at Vanderbilt Specialty Pharmacy with a proportion of days covered (PDC) < 90% in the previous 4 months are identified by a daily query of the electronic pharmacy database. A pharmacist reviews these patients' electronic health records to identify and exclude ineligible patients. Eligible patients are randomized evenly to the control or intervention arm and stratified by historical clinic nonadherence rates. Patients randomized to the intervention arm undergo a baseline assessment to clarify reasons for nonadherence and subsequently receive patient-tailored interventions based on their specific reasons. Interventions and follow-up are provided at the discretion of the intervening pharmacist. The primary outcome is PDC calculated at 8 months post-enrollment. Enrollment of 438 participants will provide 90% power to detect a 5% difference in PDC between the two arms within each nonadherence risk stratum. Discussion This trial will evaluate the effect of patient-tailored interventions on specialty medication adherence and will inform how often and why patients are misidentified as nonadherent. Registration The trial was deemed a quality improvement initiative by the Vanderbilt University Institutional Review Board. It was registered in ClinicalTrials.gov (NCT03709277) on 17 October 2018.